ORIENTASI DASAR NILAI HIDUP PADA MAHASISWA PSIKOLOGI UNNES (Jurusan Psikologi, Fakultas Ilmu Pendidikan, Universitas Negeri Semarang, 2009)
Value is a basic endorsement of attitude or a disposition that directs behavior: Value as a concrete consideration or existential also a preference that motivate indvidual behavior. This research aims to find out value orientation of unnes psychology department’s students. The research done in psychology state university o semarang with 156 students as the subjects, 44 males and 112 females. The data were taken incidentally. The research results show that there is no dominant value followed by the students of psychology department semarang state university. The highest orientation value if esthetical value, then religious value, theoretical value, social value, economical value, and the last is political value. There is no different economical value between male and female. There is no diferent esthetical value between male and female. There is no different social value between male and female. There is no different political value between male and female. There is different religious value between male and female.